Peran Tokoh Masyarakat dalam Pelestarian Kearifan Lokal Pasca Ketiadaan Kepala Adat di Desa Adat Cireundeu Cimahi - Putri Nayla Ayubia; Cucu Sukmana; Asep Saepudin (Universitas Hamzanwadi, 2024)
Establishing a cultural community becomes a valuable asset capable of supporting the dissemination of cultural values. The community in Kampung Adat Cireundeu Village, Cimahi City has long upheld traditional values. This research aims to explain how the Cireundeu community can preserve and maintain its culture despite the absence of an official adat leader. Using a qualitative method with a case study approach, data collection techniques were derived from interviews, observations, and documentation studies. This research found that the Cireundeu community successfully overcame this challenge through collective leadership mechanisms and the use of modern technology. Community figures, including elders and the deputy adat leader, play a crucial role in preserving customs and traditions through the effective distribution of responsibilities and active involvement in various customary activities. Despite facing some obstacles, such as uncertainty in decision-making and suboptimal coordination, the Cireundeu community has adopted adaptive strategies that allow them to maintain cultural preservation and ensure their social continuity. This research demonstrates that even without an Indigenous leader, community strength, local figures, and local innovation can support cultural preservation in sustaining the Indigenous community.